The Meta Marriage: Links Between Older Couples' Relationship Narratives and Marital Satisfaction. Issue 4 (11th May 2016) - McCoy, Alexandra; Rauer, Amy; Sabey, Allen
Abstract : Drawing upon a relatively understudied population and a unique observational task, the current study sought to examine how older couples' interactional behaviors during a relationship narrative task were associated with marital satisfaction over time. Using observational data from a sample of 64 older, higher‐functioning married couples, we analyzed a series of Actor–Partner Independence Models (APIM) to explore how couples' interactional behaviors during a relationship narrative task were associated with spouses' marital satisfaction both concurrently and one year later. Analyses revealed that spouses' behaviors (e.g., expressions of positive affect, negative affect, communication skills, engagement) were associated with their self‐reported marital satisfaction both at the time of the narrative and with changes in marital satisfaction. We found particularly robust evidence for the role of husbands' negative affect during the narrative task in predicting changes in both spouses' marital satisfaction over time. Our results indicate that researchers and clinicians should carefully consider the influence of development on the associations between spouses' behaviors and marital satisfaction. Further, those seeking to improve marriages in later life may need to consider the meaningful role that gender appears to play in shaping the marital experiences of older couples.